Experience of therapeutic plasma exchange in rheumatic diseases: Albumin may be a suitable substitute for plasma - Zhiqian Bai; Yu Chen; Lingli Dong (Archives of Rheumatology, 2021)
Objectives: In this study, we aimed to assess the value of therapeutic plasma exchange (TPE) in the treatment of rheumatic diseases and compare the safety of different replacement fluids used in TPE. Patients and methods: A total of 727 TPE procedures in 285 patients (57 males, 228 females; mean age: 39.7±15.4 years; range, 13 to 79 years) with rheumatic diseases between January 2011 and February 2019 were retrospectively analyzed. Data including demographic and clinical characteristics of the patients were recorded. Treatment response to TPE and adverse events were evaluated in all patients. Results: Indications for TPE included 13 different disorders, with the majority being systemic lupus erythematosus (up to 50%). The mean number of TPE sessions was 2.55±1.00 per patient and the mean exchange plasma volume was 2,270±256 mL per session. Combined plasma and albumin was the most frequently used replacement fluid (69.5%), followed by albumin and plasma in 20.5% and 10.0% of episodes, respectively. Up to 73.7% (210/285) patients achieved clinical improvement after TPE treatment. Adverse events occurred in 15.1% (110/727) of all the procedures, and allergic reaction (34.5%) was the most common event. The overall incidence rate of complication was similar among the three types of replacement fluids (p=0.214). Conclusion: Based on our study results, TPE is an invasive, but safe, useful and, sometimes, essential tool with an acceptable risk/benefit ratio for most rheumatic diseases. Albumin can be used as a feasible substitute for plasma in case of shortage of blood resources.